Vernacular Architecture in the Sotavento Region of the Algarve - José Baganha (Journal of Traditional Building, Architecture and Urbanism)
The circumstance of a recent commission for work on a tourist/residential development in the area of Castro Marim in Portugal’s Algarve province led me to discover the singularity of the region known as “Sotavento”. This is the southernmost part of Portugal, with the Atlantic to the south, the Baixo Algarve to the west, and with the Algarve Calcário (also known as “Barrocal”) extending north of the Ria Formosa lagoon, sheltered by its islands, and stretching down to the town of Tavira, north to the Serra do Caldeirão, in its eastern range forming a boundary with the inner Baixo Alentejo, and east to the river Guadiana. This article arises from a study I made of the region. The regional singularities we find here are, as elsewhere, various manifestations of the way humans inhabit the landscape and build dwellings and shelters for animals as well as accommodating the activities (chiefly farming and fishing) plied here over the centuries.